Comparison of offshore and onshore wind systems with MPC five-level converter under 3Energy 4.0 - Seixas, Mafalda (2020)
This paper is about offshore/onshore wind systems under energy 4.0. A consideration is taken to account for the action of the floating motion given by the stiffness torque acting on the drive-train. The drive-train incorporates the dynamics of the floating platform and tower, resulting from the motion of the surface due to the marine wave perturbation. The performance of the multiple point clamped five-level converter is considered mainly from electrical power perspective. The simulation considers a blade pitch control fault causing an instantaneous cutoff on the capture of the wind energy to unveil the impact on the systems performance. Particularly, the fault influence on the behavior of the voltages in the capacitor banks is mitigated by selection of the suitable vectors. The multiple point clamped five-level converter with the conveniently proposed control strategy is able to recover normal operation after fault clearing.